The Impact Level of Post-Traumatic Stress Disorder (PTSD) Symptoms on the Psychological and Behavioral Health of Students at the University of Sharqiyah in the Sultanate of Oman - Al-Obaidani, Khulood Ahmed; Al-Habsi, Khawla Salim (Journal of Educational and Psychological Sciences, 2025)
This study aimed to analyze the extent to which symptoms of Post-Traumatic Stress Disorder (PTSD) affect the psychological and behavioral well-being of university students, with the goal of providing evidence-based recommendations to mitigate the impact of such disorders and enhance students’ coping capabilities. The central research question focused on: "To what extent do PTSD and its symptoms influence the mental health and behavioral adjustment of university students?"The study employed a descriptive-analytical methodology and was conducted on a purposive sample of 40 female students enrolled in the Education Department at the College of Arts and Applied Sciences, University of Al Sharqiyah (Sultanate of Oman), during the summer semester of the 2023/2024 academic year. To fulfill the study objectives, a questionnaire comprising 17 items distributed across three core dimensions was developed to measure the psychological and behavioral effects of PTSD. The tool's validity and reliability were verified through appropriate statistical procedures, and data were analyzed using means, standard deviations, and impact scores.Findings revealed that PTSD significantly affects the mental and behavioral health of the students. Specifically, 37.5% of participants were categorized within the “high impact” group, while 26% fell within the “severe impact” category—indicating elevated levels of psychological and behavioral disruption stemming from trauma exposure. The overall impact score averaged at 3.88 with a standard deviation of 1.26, denoting a high level of influence.Among the questionnaire items, the statement under the avoidance dimension—“I experience memory loss for traumatic events (psychogenic amnesia)”—ranked first with the highest mean (4.57), followed by the item under the re-experiencing dimension—“I have distressing dreams related to the traumatic event”—with a mean score of 4.34. This variability in impact levels suggests differences in students’ psychological resilience and coping abilities.In light of the results, the study recommends the development of psychological and educational interventions that take individual differences into account, strengthen coping skills and psychological flexibility, and foster a supportive academic environment that encourages open emotional expression without stigma or shame. It further advocates for expanding individual and group counseling programs and promoting effective self-help strategies to support students’ psychological and academic well-being over the long term.
Keywords: Post-Traumatic Stress Disorder; PTSD symptoms; Mental Health; University Students